Influence of Age, Educational Level, Gestational Age, Number of Child Loss, and Marital Relationship on Grief of Women after Abortion - Sinpranee, Umaporn; Limruangrong, Piyanun; Phahuwatanakorn, Wanna; Vongsirimas, Nopporn; Boriboonhirunsarn, Dittakarn (Journal of The Royal Thai Army Nurses, 2025)
This research aimed to study the influence of age, educational level, gestational age, number of child loss, and marital relationship on grief of women after abortion. The sample was 100 post-abortion women who had suffered the loss of a child at less than 28 weeks gestational age and had medical indications for abortion. The sample were admitted at The Thammasat University Hospital and Siriraj Hospital. Data were collected by using questionnaires on demographic data, the dyadic adjustment scale, and the perinatal grief scale. The data were analyzed by using descriptive statistics and multiple regression analysis. According to the findings, the sample had a mean score of 84.7 points (SD=24.6) for grief on the date of treatment after abortion. The factors with influence over women’s grief following abortion were age (β = -.235, p = .013), number of child losses (β = .324, p = .001), and marital relationship (β = -.204, p = .029). The variances in women’s grief scores after abortion were explained by 22.30% (R2 = .223, F = 5.396, p<.001). Recommendations: Women who had an abortion at a young age, a history of child loss, and poor marital relationships can lead to a high level of grief. Therefore, risk screening should be performed in order to plan support to enable women to work through the process of grief appropriately.